2018
DOI: 10.3889/oamjms.2018.287
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life in Children with Asthma versus Healthy Children

Abstract: BACKGROUND:Asthma is the most prevalent chronic disease in the pediatric age group. The disease affects different aspects of the children’s lives, such as physical, emotional, social and educational aspects. Thus, more focus has been on the quality of life in these patients rather than the duration of their illness in recent years.AIM:This study examined the different aspects of quality of life in asthmatic children for the first time in this geographic area.METHODS:The study was cross-sectional conducted in 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 23 publications
1
32
1
2
Order By: Relevance
“…Overall, the results of this study were closely associated with a significant low Parallel to current findings, a vast number of previous studies have demonstrated a meaningful drop in the QoL of patients suffering from asthma at different ages. For example, Kouzegaran et al, who investigated the QoL associated with asthma in 8 -12-year-old children using the standard PedsQL questionnaire in 2019, reported asthma as a prevalent chronic disease that puts the most significant burden on the QoL of asthmatic children (14,15,24). Ultimately, after assessing different aspects and components of QoL, despite the social performance, these children were found to have the most considerable drop in physical, emotional, and academic performance (14).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Overall, the results of this study were closely associated with a significant low Parallel to current findings, a vast number of previous studies have demonstrated a meaningful drop in the QoL of patients suffering from asthma at different ages. For example, Kouzegaran et al, who investigated the QoL associated with asthma in 8 -12-year-old children using the standard PedsQL questionnaire in 2019, reported asthma as a prevalent chronic disease that puts the most significant burden on the QoL of asthmatic children (14,15,24). Ultimately, after assessing different aspects and components of QoL, despite the social performance, these children were found to have the most considerable drop in physical, emotional, and academic performance (14).…”
Section: Discussionmentioning
confidence: 99%
“…For example, Kouzegaran et al, who investigated the QoL associated with asthma in 8 -12-year-old children using the standard PedsQL questionnaire in 2019, reported asthma as a prevalent chronic disease that puts the most significant burden on the QoL of asthmatic children (14,15,24). Ultimately, after assessing different aspects and components of QoL, despite the social performance, these children were found to have the most considerable drop in physical, emotional, and academic performance (14). In a meta-analysis study in Portugal, Silva et al compared the HRQoL of 1797 asthmatic children and 13266 healthy controls and observed a low total score, while the most significant operative impairments in terms of physical and social factors and psychiatric comorbidity were observed in children with asthma rather than in healthy subjects, which is consistent with the current data (25).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… 9 In general, when compared to healthy children of the same age, children with asthma, especially poorly controlled asthma, were noted to have a lower quality of life in physical performance, emotional performance, and school performance. 10 …”
mentioning
confidence: 99%